Teaching methodology and its influence on the development of productive skills with the adult students of the Canadian House Center, academic period 2012-2013 - Jiménez Quezada, Marylin Kastiuska (2014)
The present research work was developed in order to identify the influence of teaching methodology on the development of productive skills with the adult students of The Canadian House Center. The scientific method was used as a research tool in order to gather data and confirm ideas. The analytical-synthetic method was also used to analyze the main results; the descriptive method to describe the data and the explicative method to explain the phenomena. Surveys were applied to whole the population, which included 100 adult students and 8 teachers. The most relevant results found through this research showed that teachers were using obsolete methods in the English Language teaching process. Moreover, teachers were applying a limited number of techniques for developing the students’ productive skills. This demonstrated that students do not have sufficient opportunities to improve writing and speaking skills. Therefore, based on the findings it was determined that the teaching methodology used influenced negatively on the development of the productive skills due to students do not acquire a proficient level in their English skills.